Two Different Bacillus thuringiensis Delta-Endotoxin Receptors in the Midgut Brush Border Membrane of the European Corn Borer, Ostrinia nubilalis (Hübner) (Lepidoptera: Pyralidae) - Denolf, P. (1993)
Binding of three Bacillus thuringiensis insecticidal crystal proteins (ICPs) to the midgut epithelium of Ostrinia nubilalis larvae was characterized by performing binding experiments with both isolated brush border membrane vesicles and gut tissue sections. Our results demonstrate that two independent ICP receptors are present in the brush border of O. nubilalis gut epithelium. From competition binding experiments performed with (125)I-labeled and native ICPs it was concluded that CryIA(b) and CryIA(c) are recognized by the same receptor. An 11-fold-higher binding affinity of CryIA(b) for this receptor correlated with a 10-fold-higher toxicity of this ICP compared with CryIA(c). The CryIB toxin did not compete for the binding site of CryIA(b) and CryIA(c). Immunological detection of ingested B. thuringiensis ICPs on gut sections of O. nubilalis larvae revealed binding only along the epithelial brush border membrane. CryID and CryIE, two ICPs that are not toxic to O. nubilalis, were not bound to the apical microvilli of gut epithelial cells. In vitro binding experiments performed with native and biotinylated ICPs on tissue sections confirmed the correlation between ICP binding and toxicity. Moreover, by performing heterologous competition experiments with biotinylated and native ICPs, it was confirmed that the CryIB receptor is different from the receptor for CryIA(b) and CryIA(c). Retention of activated crystal proteins by the peritrophic membrane was not correlated with toxicity. Furthermore, it was demonstrated that CryIA(b), CryIA(c), and CryIB toxins interact in vitro with the epithelial microvilli of Malpighian tubules. In addition, CryIA(c) toxin also adheres to the basement membrane of the midgut epithelium.